Partial Glycerides Synthesis by Lipase of Aspergillus niger - H. L., Chin; Che Omar, Ibrahim (Universiti Putra Malaysia Press, 1995)
The lipase of Aspergillus niger was examined for partial glycerides synthesis. A significant degree of synthesis (more than 50%) was achieved using lamate as one of the substrates. This can be further improved by optimizing the reaction conditions. A synthesis degree of almost 80% was obtained in the presence of 3.0 g of molecular sieve pellets for water absorption in the reaction system.